Challenges of genetic diagnosis of inborn errors of metabolism in a major tertiary care center in Lebanon - Salman, Doaa O.; Mahfouz, Rami; Bitar, Elio R.; Samaha, Jinane; Karam, Pascale E. (Frontiers in Genetics, 2022)
Background: Inborn errors of metabolism are rare genetic disorders; however, these are prevalent in countries with high consanguinity rates, like Lebanon. Patients are suspected, based on a combination of clinical and biochemical features; however, the final confirmation relies on genetic testing. Using next generation sequencing, as a new genetic investigational tool, carries several challenges for the physician, the geneticist, and the families. Methods: In this retrospective study, we analyzed the clinical, biochemical, and genetic profile of inborn errors of metabolism suspected patients, seen at a major tertiary care center in Lebanon, between 2015 and 2018. Genetic testing was performed using next generation sequencing. Genotype-phenotype correlation and diagnostic yield of each testing modality were studied. Results: Out of 211 patients genetically tested, 126 were suspected to have an inborn error of metabolism. The diagnostic yield of next generation sequencing reached 64.3%. Single gene testing was requested in 53%, whole exome sequencing in 36% and gene panels in 10%. Aminoacid disorders were mostly diagnosed followed by storage disorders, organic acidemias and mitochondrial diseases. Targeted testing was performed in 77% of aminoacid and organic acid disorders and half of suspected storage disorders. Single gene sequencing was positive in 75%, whereas whole exome sequencing diagnostic yield for complex cases, like mitochondrial disorders, reached 49%. Good clinical and biochemical correlation allowed the interpretation of variants of unknown significance and negative mutations as well as therapeutic management of most patients. Conclusion: Tailoring the choice of test modality, by next generation sequencing, to the category of suspected inborn errors of metabolism may lead to rapid diagnosis, shortcutting the cost of repeated testing. Whole exome sequencing as a first-tier investigation may be considered mainly for suspected mitochondrial diseases, whereas targeted sequencing can be offered upon suspicion of a specific enzyme deficiency. Timing and modality of gene test remain challenging, in view of the cost incurred by families.